Analysis of the Shear Resistance Force of Filled Gravels Confined in a Flexible Frame Using an Assembled Distinct Element Method. Issue 2 (June 2014) - Horiguchi, T.; Katsuki, S.
In this paper, we propose a distinct element method (DEM) for estimating the shear resistance force of filled gravels in stair-shaped and flexible steel frames such as a gabion. The filled gravels were modelled by the DEM, using assembled elements to take into consideration the roughness of their surfaces, which produced interlocking and rotational resistance, among other effects. The assembled elements used in this study consisted of six similar-sized overlapping spherical elements symmetrically arranged in the shape of a regular octahedron. The ratio of the non-overlapped depth to the diameter of the spherical elements was termed the protruding coefficient β, which could be used to control the internal friction angle of the filled gravels and represent their dilatancy. The angle of repose of the gravels, which were filled in a stair-shaped steel frame check dam or a flexible steel frame such as a gabion, could be easily measured in the field. By inserting the value the experimental angle of repose into the relationship between the analytical angle of repose and the protruding coefficient β, the protruding coefficient β of the gravel model is obtained. The analytical angle of repose obtained by the assembled element model was identical with the value experimentally determined for the adopted gravels. The experimental results for both the stair-shaped frame and the real-size gabion were simulated using the proposed method to evaluate the shear resistance force. The analytical and experimental results were observed to be in good agreement.